A controversial role of neutrophils in tuberculosis infection pathogenesis - I. A. Linge; A. S. Apt (Инфекция и иммунитет, 2021)
Tuberculosis (TB) continues to be an important and unresolved medical problem. About a quarter of mankind is infected with Mycobacterium tuberculosis, and about 5–10% of these people eventually develop TB. Macrophages and CD4+ T cells are considered the key cells providing defense against TB infection. The role of neutrophils in TB is less well defined. Neutrophils are short-lived granulocytes among first migrate into the infectious lung tissue and phagocy tose mycobacteria. On the one hand, there is evidence for protective role of neutrophils in TB released via anti-microbial peptides inhibiting mycobacterial growth, up-regulation of CD4+ T-cell activation, and dendritic cell migration in the lymph nodes. On the other hand, infection of genetically TB susceptible animals leads to an overwhelming lung neutrophil inflammation, development of necrotic granulomata, and a rapid death. Neutrophils act directly or indirectly on mycobacteria by different oxidative or other reactions including neutrophil extracellular traps (NETs) formation. Phagocytosis of mycobacteria by neutrophils is accompanied by the production of pro-inflammatory factors, thus making neutrophils active participants of inflammation in all stages of the infectious process. Finally, neutrophils die by apoptosis or necrosis. Necrosis of neutrophils, which is activated by reactive oxygen species, also prolongs the inflammation. In this way, there is strong evidence that neutrophils are the cells involved in the transition of infection to the terminal stage, participating in lung tissue destruction. Although neutrophils evolutionary developed many ways to resist pathogens, it is likely, that neutrophils do not possess sufficient anti-mycobactericidal capacities due to the development of many adaptations allowing mycobacteria to survive inside the neutrophils. Neutrophils effectively phagocytose but poorly kill mycobacteria, thus hiding bacilli from more efficient killers, macrophages, and playing the role of the “Trojan Horse”. In this review, we summarize the data on the involvement of neutrophils in TB inflammation. We discuss their ambiguous role in pathogenesis which depends upon mycobacterial virulence, host genetics, dynamics of migration to inflammatory foci, and persistence during initial and chronic stages of the infectious process.